2016
DOI: 10.1016/j.vaccine.2015.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Global Vaccine and Immunization Research Forum: Opportunities and challenges in vaccine discovery, development, and delivery

Abstract: The World Health Organization, the National Institute of Allergy and Infectious Diseases, part of the National Institutes of Health, and the Bill & Melinda Gates Foundation convened the first Global Vaccine and Immunization Research Forum (GVIRF) in March 2014. This first GVIRF aimed to track recent progress of the Global Vaccine Action Plan research and development agenda, identify opportunities and challenges, promote partnerships in vaccine research, and facilitate the inclusion of all stakeholders in vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…TPPs describe the minimally acceptable and aspirational ranges of product features to guide product PLOS ONE development of vaccines, and establish go/no-go criteria for prioritisation and investment by developers. As such, the TSE approach could allow manufacturers to understand country needs, which could be combined with technical considerations such as likelihood of clinical success and manufacturing feasibility to develop more robust TPPs and roadmaps for products with higher chance of country uptake that will ultimately lead to greater public health impact [19]. This study demonstrated the application of MCDA as systematic approach for evaluating the relative value proposition, or trade off, of existing and potential products based on country priorities.…”
Section: Discussionmentioning
confidence: 99%
“…TPPs describe the minimally acceptable and aspirational ranges of product features to guide product PLOS ONE development of vaccines, and establish go/no-go criteria for prioritisation and investment by developers. As such, the TSE approach could allow manufacturers to understand country needs, which could be combined with technical considerations such as likelihood of clinical success and manufacturing feasibility to develop more robust TPPs and roadmaps for products with higher chance of country uptake that will ultimately lead to greater public health impact [19]. This study demonstrated the application of MCDA as systematic approach for evaluating the relative value proposition, or trade off, of existing and potential products based on country priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Main focus of GVIRF is on current vaccine development specifically for the treatment of human immunodeficiency virus (HIV), tuberculosis (TB), malaria and universal influenza vaccines. 28 On this forum, research strategy and molecular mechanism concerning these vaccines are discussed in detail. HIV is famous for its previous name 'acquired immune deficiency syndrome (AIDS)', which has the abilities of progressively causing failure of the immune system and life-threatening opportunistic infections.…”
Section: Hiv Vaccinesmentioning
confidence: 99%
“…Based on the 2017 assessment report of the GVAP, however, progress continues to be slow and likely most of its 2020 goals may be challenging to reach. 36,37 For instance, indicator data suggest that vaccine coverage levels are not increasing and diseases outbreaks such as measles and others continue to occur. These challenges are due to multiple global, regional and national issues which will require increased global efforts to promote more R&D, increase immunization campaigns, reduce vaccine hesitancy and address the systemic weaknesses that are limiting equitable vaccine access.…”
Section: Business Case and Full Public Health Value Proposition For Nmentioning
confidence: 99%